2015
DOI: 10.1099/jgv.0.000027
|View full text |Cite
|
Sign up to set email alerts
|

Vif determines the requirement for CBF-β in APOBEC3 degradation

Abstract: APOBEC3 (apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3) proteins are cellular DNA deaminases that restrict a broad spectrum of lentiviruses. This process is counteracted by Vif (viral infectivity factor) of lentiviruses, which binds APOBEC3s and promotes their degradation. CBF-b (core binding factor subunit b) is an essential co-factor for the function of human immunodeficiency virus type 1 Vif to degrade human APOBEC3s. However, the requirement for CBF-b in Vif-mediated degradation of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…However, some cross degradation was observed as might also be expected because the A3 enzymes are relatively conserved (especially in comparison to Vif). Surprisingly, recent work has demonstrated that CBF-β is specifically required for function of primate lentiviral Vif proteins, but not for non-primate Vifs (Ai et al, 2014; Han et al, 2014; Yoshikawa et al, 2014; Zhang et al, 2014). These data indicate that either the Vif proteins of FIV, BIV, and MVV do not require a CBF-β-like factor, or these viruses have evolved to use one or more other as-yet-unknown cellular factors.…”
Section: Human Apobec3 Enzymes and Hiv Restrictionmentioning
confidence: 99%
“…However, some cross degradation was observed as might also be expected because the A3 enzymes are relatively conserved (especially in comparison to Vif). Surprisingly, recent work has demonstrated that CBF-β is specifically required for function of primate lentiviral Vif proteins, but not for non-primate Vifs (Ai et al, 2014; Han et al, 2014; Yoshikawa et al, 2014; Zhang et al, 2014). These data indicate that either the Vif proteins of FIV, BIV, and MVV do not require a CBF-β-like factor, or these viruses have evolved to use one or more other as-yet-unknown cellular factors.…”
Section: Human Apobec3 Enzymes and Hiv Restrictionmentioning
confidence: 99%
“…This cross-species “jump” was most likely facilitated by hijacking CBF-β to counteract APOBEC3-mediated restriction through the aforementioned two-pronged mechanism (Fig 1D). In support of this model, SIV Vif still has the capacity to degrade feline APOBEC3 enzymes in a CBF-β dependent manner [10, 24, 25]. Moreover, this newly transmitted virus most likely initially produced a Vif protein capable of suboptimal degradation of the APOBEC3 enzymes of its new host.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we used an in vitro cell culture system to evaluate whether FIVpco Vif can degrade feline APOBEC3 proteins. For this assay, we obtained the FLAG‐tagged codon‐optimized open reading frames of FIVfca Vif strain Petaluma , FIVfca strain C36 and FIVpco strain PLV1695 from GeneArt Gene Synthesis service (Life Technologies, Carlsbad, CA, USA) (the GenBank accession numbers are presented in the legend of Figure , and the codon‐optimized sequences are available on request). The obtained DNA fragments were inserted the Bam HI‐ Sal I site of pDON‐AI plasmid (Takara, Kyoto, Japan).…”
mentioning
confidence: 99%
“…We co‐transfected these plasmids into HEK293T cells by using PEI Max (Polysciences, Warrington, PA, USA) and harvested the cells and viral particles from culture supernatants at 48 hr post‐transfection. The harvested samples were used for SDS‐PAGE/western blotting or lentiviral reporter assays as previously described . Briefly, we used the following antibodies for western blotting: an anti‐FLAG polyclonal antibody (Sigma, St Louis, MO, USA), an anti‐HA antibody (3F10; Roche, Indianapolis, IN, USA), an anti‐FIV p27 Capsid antibody (PAK3‐2C1; Santa Cruz Biotechnology, Santa Cruz, CA, USA); an anti‐α‐tubulin antibody (DM1A; Sigma) and an anti‐VSVg antibody (P5DA; Roche).…”
mentioning
confidence: 99%